Assessing the health and economic burden of obesity-related complications in East-Asian populations: implementation of risk equations in the Core Obesity Model for Japan and model validation - Ichiro Tatsuno; Mark Lamotte; Laetitia Gerlier; Anamaria-Vera Olivieri; James Baker-Knight (BMJ Public Health)
Objective Obesity is associated with a significant clinical and economic burden and its prevalence has reached epidemic proportions worldwide. An ethnicity-specific impact of excess weight has been demonstrated, with Asian individuals exhibiting weight-related health problems at lower body mass indexes (BMIs) than Caucasians. We aimed to adapt the core obesity model (COM) to predict incidences of weight-associated diseases, including type 2 diabetes, acute coronary syndrome (ACS), stroke, cancers, sleep apnoea, hyperuricaemia/gout, total knee replacement (TKR) and non-alcoholic fatty liver disease (NAFLD) in a Japanese population.Methods and analysis Literature was searched to identify studies reporting the association between risk factors and comorbidities in Japanese populations. Data were extracted to update the COM risk prediction equations. Internal and external validation were performed.Results Overall, good internal validity was achieved, with mild underestimation for diabetes, cardiovascular and all-cause death taken together (ordinary least squares linear regression [OLS-LRL] 0.8844), moderate overestimation of TKR and cancers (OLS-LRL 1.267) and a slight underestimation for NAFLD and hyperuricaemia (OLS-LRL 0.934). External validation results were aligned with known geographical patterns: complications occurred at lower BMI in Japanese individuals, with a threefold higher incidence of diabetes and twofold higher obstructive sleep apnoea, gout prevalence and colorectal cancer at equal BMI. Conversely, the 10-year cumulative ACS incidences predicted in a Japanese population were less than half of those in a Western population.Conclusion The Japanese COM adaptation addresses ethnicity-specific patterns of overweight/obesity, with better sensitivity to lower BMIs for several associated complications. It may support regional public health policy and research.